A conceptual framework for market orientation and organizational performance in takaful business in Malaysia. - Norizan, Remli; Wan Norhayate, Wan Daud (2011)
The aim of this paper is to propose a conceptual framework in order to study the market orientation an organizational performance in takaful business in Malaysia. Clearly the framework suggests that market orientation would influence performance of the organization.Innovation would be considered as the mediator factor in the relationship. From the review of literatures,hyphotheses are developed to suggest the relationship between the market orientation, innovation and performance.